Analytic Entrepreneurial Spirit of Udayana University Student - A. C., Rofiah; Putri, B. R. T.; Inggriati, N. W. T. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
The high level of population growth and many of unemployed is a classic problem in developing countries, including in Indonesia, the number of unemployed increased every year. In 2013 until 2016 the number of working generation who didn’t have jobs or open unemployment in Bali increased from 41,820 people (0,9%) to 46,484 people (1,1%) than total population in Bali (4,2 million people). Unemployment in Indonesia occurs at all level of education including undergraduate degrees. The Central of Statistics showed that undergraduate numbers unemployed in Indonesia in the past three years was increase. Based on data, show that college graduates still oriented as job seekers. The purpose of this study to know role of entrepreneurship deliver the spirit student entrepreneurship. The research design is using survey research with qualitative and quantitative methods, with a total sample 60 students from 13 faculties at Udayana University. The data source uses primary data, that is direct interviews. This study uses descriptive analysis and factor analysis. The research result show that students who get entrepreneurship course and practice have a higher entrepreneurial spirit than students who get entrepreneurship course only and students who don’t get entrepreneurship courses with indicators of self-confidence (100%), innovative (70%), creative (90%), and leadership spirit (95%). Students who are given entrepreneurship and practicum course have a higher in entrepreneurial spirit ( koef 0,999) than students who are given entrepreneurship course only ( koef 0,750) and who don’t give entrepreneurship course ( koef 0,691).   Keywords: entrepreneurial spirit, entrepreneurship, students, unemployment